A survey of stroke‐related capabilities among a sample of US community emergency departments. Issue 4 (22nd July 2022) - Zachrison, Kori S.; Ganti, Latha; Sharma, Dhruv; Goyal, Pawan; Decker‐Palmer, Marquita; Adeoye, Opeolu; Goldstein, Joshua N.; Jauch, Edward C.; Lo, Bruce M.; Madsen, Tracy E.; Meurer, William; Oostema, John A.; et al.
Abstract: Objectives: Most acute stroke research is conducted at academic and larger hospitals, which may differ from many non‐academic (ie, community) and smaller hospitals with respect to resources and consultant availability. We describe current emergency department (ED) and hospital‐level stroke‐related capabilities among a sample of community EDs participating in the Emergency Quality Network (E‐QUAL) stroke collaborative. Methods: Among E‐QUAL‐participating EDs, we conducted a survey to collect data on ED and hospital stroke‐related structural and process capabilities associated with quality of stroke care delivery and patient outcomes. EDs submitted data using a web‐based submission portal. We present descriptive statistics of self‐reported capabilities. Results: Of 154 participating EDs in 30 states, 97 (63%) completed the survey. Many were rural (33%); most (82%) were not certified stroke centers. Although most reported having stroke protocols (67%), many did not include hemorrhagic stroke or transient ischemic attack (45% and 57%, respectively). Capability to perform emergent head computed tomography and to administer thrombolysis were not universal (absent in 4% and 5%, respectively). Access to neurologic consultants varied; 18% reported no 24/7 availability onsite or remotely. Of those with access, 48% reported access through telemedicine only. Admission capabilities also varied with patient transfer commonly performed (79%). Conclusion: Stroke‐related capabilities vary substantially between community EDs and are different from capabilities typically found in larger stroke centers. These data may be valuable for identifying areas for future investment. Additionally, the design of stroke quality improvement interventions and metrics to evaluate emergency stroke care delivery should account for these key structural differences.